The effectiveness of nutrition education on mother's knowledge and the pattern of infant and child feeding in Kapetakan District, Cirebon Regency, West Java - Pipit Choliyah (ARGIPA (Arsip Gizi dan Pangan), 2020)
Feeding infants and toddlers (PMBA) is one of the government programs to reduce child mortality. PMBA include early breastfeeding initiation (IMD), exclusive breastfeeding, complementary food and breastfeeding up to 2 years old. The survey results in Pegagan Lor village, the case of malnutrition in Kapetakan sub-district was higher than national, which was 23%. The purpose of this study was to determine the effectiveness of providing nutrition education on maternal knowledge and feeding patterns of infants and toddlers. This research type was quasi-experimental with a control group pre-test and post-test design. The sample of this research is 70 mothers of toddlers who have children aged 6 to 24 months. The inclusion criteria in this study were mothers of toddlers who could read and write, and were willing to be respondent. The sample was divided into two groups of intervention and control group. In the intervention group was given nutrition education and booklets, while in the control group was only booklet. Data processing on knowledge variable used the paired sample t-test, and the feeding infants and toddlers pattern used the Wilcoxon sign test. Based on the results of the research that has been carried out, it can be concluded that the provision of nutrition education and booklet was more effective in changing knowledge and patterns of giving feeding infants and toddlers compared to only providing booklet. Providing nutrition education and booklets can provide changes in the direction of better maternal knowledge and feeding infants and toddlers pattern.